2022
DOI: 10.3389/fonc.2022.913438
|View full text |Cite
|
Sign up to set email alerts
|

Advancements in the treatment of metastatic hormone-sensitive prostate cancer

Abstract: In the last decade, there have been substantial improvements in the outcome of the management of metastatic hormone-sensitive prostate cancer (mHSPC) following the development of several novel agents as well as by combining several therapeutic strategies. Although the overall survival (OS) of mHSPC is shown to improve with intense androgen deprivation therapy (ADT), combined with docetaxel, as well as other novel hormonal therapy agents, or alongside local intervention to the primary neoplasm. Notably, luteini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…As a semisynthetic taxane, docetaxel exhibits significant single-agent activity against PCa, mainly by inhibiting microtubules polymerization and inducing cell cycle arrest at the G2/M phase and subsequent apoptosis [7] . In recent trials, the combined use of docetaxel and ADT significantly improved the overall survival of patients with metastatic, hormone-sensitive PCa, particularly with high tumor volumes [ 8 , 9 ]. These promising data indicated that docetaxel would remain a mainstay for the clinical management of PCa [10] .…”
Section: Introductionmentioning
confidence: 99%
“…As a semisynthetic taxane, docetaxel exhibits significant single-agent activity against PCa, mainly by inhibiting microtubules polymerization and inducing cell cycle arrest at the G2/M phase and subsequent apoptosis [7] . In recent trials, the combined use of docetaxel and ADT significantly improved the overall survival of patients with metastatic, hormone-sensitive PCa, particularly with high tumor volumes [ 8 , 9 ]. These promising data indicated that docetaxel would remain a mainstay for the clinical management of PCa [10] .…”
Section: Introductionmentioning
confidence: 99%